SootImage: An image recreation, post-processing validation procedure for sooting axisymmetric flames - Chernov, V.; Escudero, F.; Cruz Villanueva, J.J.; Eaves, N.A.; Fuentes, A. (Elsevier, 2024)
Validation is a vital part of any computational fluid dynamics study. Validation is done by comparing the computed results to the experimental measurements performed in a known configuration. In sooting flames, such a comparison is non-trivial since the measurements have a wide range of uncertainty due to difficulties in directly measuring soot volume fractions. This work introduces a different way to verify the computations using a software package called SootImage. In this proposed methodology, comparisons are not made directly to the computed properties of interest (soot volume fraction and temperature). Instead, a post-processing procedure is performed to obtain an image of the flame based on the computed properties. This reconstructed image is compared to an actual image of the flame being studied. The algorithm of the image reconstruction utilized within SootImage is presented in detail. Finally, the usage of SootImage is demonstrated on a co-flowing, laminar ethylene/air diffusion flame
Keywords: Digital Image Processing; Data Validation; https://purl.org/pe-repo/ocde/ford#1.02.00